The effect of ocular reflex exercises using a proposed device on eyes - hands coordination for junior boxers - Naser, A. J. (Journal Mustansiriyah of Sports Science, 2022)
When the researcher reviewed the training curricula for boxing coaches, he found that most of them focus on physical and motor abilities, skills and plans, and do not give much attention to some important boxing exercises, such as hand-eye coordination exercises., the aim of the research was to design a proposed device and know the frequency of its use in developing the compatibility between the eyes and hands for the budding boxers. The research sample consisted of eight boxers, and after applying the exercises to the proposed device, the researcher concluded that the exercises for using the proposed device have a positive effect in developing the compatibility between the eyes and the arms, and that visual vision exercises are very important in the sport of boxing to develop compatibility between the eyes and hands.